Absolute forecast errors of earnings in Malaysian IPO prospectuses: The impact of ethnic diversity - Ammer, Mohammed Abdullah; Ahmad Zaluki, Nurwati Ashikkin (Penerbit UTM Press, 2014)
The main focus of this paper is the earnings forecast, a vital information included in IPO prospectus.Specifically, our paper examined the impact of ethnic diversity groups on the boards of directors and audit committees in terms of earnings forecast accuracy.We are motivated by the lack of prior studies related to investigating IPO earnings forecast.Cross-sectional Ordinary Least Squares (OLS) modeling was conducted on 190 Malaysian IPOs from 2002 to 2012.For the evaluation of earnings forecast accuracy, we mathematically used the metric of Absolute Forecast Error (AFER).Moreover, for the test of robustness, we used the metric of Squared Forecast Error (SQFER) as error measurement, as it mostly deals with large errors.The empirical results indicate that the ethnic diversity groups on boards and audit committees have an impact on the accuracy of earnings forecasts.However, the evidence is significant for Chinese and Malay serving on boards but insignificant in terms of Chinese and Malay serving on audit committee.The findings indicate that multi-ethnic groups in Malaysian IPO companies could hinder the capability of IPO companies to achieve accurate earnings forecasts in their prospectuses.